2021
DOI: 10.1155/2021/5515941
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for COVID-19 in Patients with Hypertension

Abstract: Background. Hypertension, as the most common comorbidity for patients with coronavirus disease 19 (COVID-19), has resulted in cases with more severe symptoms and higher mortality. The risk factors associated with COVID-19 in patients with hypertension are unknown. Methods. All the available and confirmed patients with COVID-19 from February 3 to March 10, 2020, were enrolled from Huoshenshan Hospital, Wuhan, China. The demographic characteristics, clinical manifestations, laboratory data, radiological assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 21 publications
1
9
0
1
Order By: Relevance
“…47 Although our study does not include laboratory parameters for their evaluation as prognostic markers there are previous data for the same. 29,36,37,40,[52][53][54][55][56][57][58][59] Increase in indicators such as neutrophils, neutrophil-leukocyte ratio, lactate dehydrogenase, troponin, d-dimer, C-reactive protein, creatinine, urea, interleukins, and markers of cardiac injury have been associated with a poorer prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…47 Although our study does not include laboratory parameters for their evaluation as prognostic markers there are previous data for the same. 29,36,37,40,[52][53][54][55][56][57][58][59] Increase in indicators such as neutrophils, neutrophil-leukocyte ratio, lactate dehydrogenase, troponin, d-dimer, C-reactive protein, creatinine, urea, interleukins, and markers of cardiac injury have been associated with a poorer prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Since the onset of COVID‐19, HTN has been found to be a major risk factor in patients. 3 The incidence of HTN and COVID‐19 were reported by the Chinese Center for Disease Control to be 12.8% worldwide, while other studies have reported as high as 30% and 31%. 4 , 5 Angiotensin‐converting enzyme (ACEi) and angiotensin receptor blockers (ARB) are the most widely prescribed antihypertensives in the market.…”
Section: Introductionmentioning
confidence: 99%
“…According to Yang et al, 2 the patients with COVID‐19 with comorbidity of hypertension (HTN) had a higher death rate (10.3%) and were more critically ill (18.3%) as compared with individuals without HTN. Since the onset of COVID‐19, HTN has been found to be a major risk factor in patients 3 . The incidence of HTN and COVID‐19 were reported by the Chinese Center for Disease Control to be 12.8% worldwide, while other studies have reported as high as 30% and 31% 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, hypertensive patients had been observed to have a higher proportion of pulmonary infection and an increased risk for severe adverse COVID-19 outcomes [7].…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is also another risk factor for worsening the COVID-19 disease across various ethnicities [ 6 ]. In addition, hypertensive patients had been observed to have a higher proportion of pulmonary infection and an increased risk for severe adverse COVID-19 outcomes [ 7 ].…”
Section: Introductionmentioning
confidence: 99%